2013
DOI: 10.1007/s12088-013-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nutrient Requirements and Culture Conditions for the Production of Rhamnolipid from Pseudomonas aeruginosa (MTCC 7815) using Mesua ferrea Seed Oil

Abstract: Environmental awareness has led to a serious consideration for biological surfactants and hence nonedible vegetable oils may serve as a substitute carbon source for bio-surfactant production (rhamnolipid) which might be an alternative to complex synthetic surfactants. There are reports of rhamnolipid production from plant based oil giving higher production than that of glucose because of their hydrophobicity and high carbon content. Therefore the contribution of non-edible oil such as Mesua ferrea seed oil cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A wide range of rhamnolipid production yield by Pseudomonas species using vegetable oils and/or their wastes as carbon source has been reported. P. aeruginosa produced rhamnolipid when grown on water-insoluble substrates such as coconut oil (2.26 g/L) (George and Jayachandran 2013), Mesua ferrea seed oil (6.95 g/L) (Singh et al 2013), soy bean oil (12 g/L) (Abbasi et al 2012), waste cooking oil (13.93 g/L) (Lan et al 2015), waste frying oil (6.6 g/L) (Luo et al 2013), and waste frying oil (24.61 g/L) (Zhu et al 2007). The rhamnolipid yield achieved in the present study with P. aeruginosa OG1 (13.31 g/L) using waste frying oil and CFP at optimal concentrations was much greater than the yields obtained in several previous studies.…”
Section: Validation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of rhamnolipid production yield by Pseudomonas species using vegetable oils and/or their wastes as carbon source has been reported. P. aeruginosa produced rhamnolipid when grown on water-insoluble substrates such as coconut oil (2.26 g/L) (George and Jayachandran 2013), Mesua ferrea seed oil (6.95 g/L) (Singh et al 2013), soy bean oil (12 g/L) (Abbasi et al 2012), waste cooking oil (13.93 g/L) (Lan et al 2015), waste frying oil (6.6 g/L) (Luo et al 2013), and waste frying oil (24.61 g/L) (Zhu et al 2007). The rhamnolipid yield achieved in the present study with P. aeruginosa OG1 (13.31 g/L) using waste frying oil and CFP at optimal concentrations was much greater than the yields obtained in several previous studies.…”
Section: Validation Of the Modelmentioning
confidence: 99%
“…Feather, a waste by-product of industrial poultry-processing plants, was shown to be an effective nitrogen source supporting the microbial growth (Taskin and Kurbanoglu 2011). The presence of amino acids (especially isoleucine) and several micronutrients (e.g., K, Fe, P, Mg, S, and Ca salts) stimulates rhamnolipid production in P. aeruginosa (Lotfabad et al 2009;Nawawi et al 2010;Singh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a hydrophobic substrate such as SAO using pseudomonas species yields maximum 4.9 g L −1 RL, whereas the same strain gives lower yield when hydrophilic sources are used as carbon substrates (Wadekar et al, ). The long alkyl chain of hydrophobic substrates compared to hydrophilic sources that supply carbon sources to the cells is the key attribute of higher production yield (Singh et al, ). In addition, rhamnolipid production by different microbial strains can be increased by increasing water availability of water‐immiscible substrates through emulsification.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, much attention has been intended for biosurfactant owing to their advantages such as biodegra dability, low toxicity, lower critical micelle concentration, environmental compatibility, higher specificity and better activity at extreme conditions like high temperature, high pH and high salinity (Banat, 1995;Cameotra et al, 1998;Ron and Rosenberg, 2001; VanHamme et al, 2006;Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%